Embedded Jawi Script Generator - Rohani, S. Mohamed Farook; Zulkifli, Hussin; Noor Shalasiah, Osman (Malaysia Association of Research Scientists (MARS), 2010)
Rohani S. Mohamed Farook and her team won silver at Malaysia Technology Expo 2010 (MTE 2010), 4th - 6th February 2010 at Putra World Trade Centre (PWTC), Kuala Lumpur. MTE 2010 organized by MARS and PROTEMP Exhibitions Sdn. Bhd.